2022
DOI: 10.3389/fpsyg.2022.813624
|View full text |Cite
|
Sign up to set email alerts
|

Examining Multiteam Systems Across Context and Type: A Historiometric Analysis of Failed MTS Performance

Abstract: Multiteam systems (MTSs) are complex organizational forms comprising interdependent teams that work towards their own proximal goals within and across teams to also accomplish a shared superordinate goal. MTSs operate within high-stakes, dangerous contexts with high consequences for suboptimal performance. We answer calls for nuanced exploration and cross-context comparison of MTSs “in the wild” by leveraging the MTS action sub-phase behavioral taxonomy to determine where and how MTS failures occur. To our kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Yet, ironically, it has been found that sub‐teams working within MTSs tend to prioritize intra‐team over inter‐team communications (Allen et al, 2014; Wang et al, 2015). This tendency to favour intra‐team communications is more likely to happen when under stress (Campbell et al, 2022) and when organizations lack a culture of information sharing (Bharosa et al, 2010; Kwon et al, 2011). Within emergency response contexts, it has been shown that processes for information sharing are not embedded; the Manchester Arena Inquiry (Saunders, 2022) noted there was a failure to identify who needed specific pieces of information, there were no clear radio channels to communicate information, and agencies failed to co‐locate at the scene limiting communications.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, ironically, it has been found that sub‐teams working within MTSs tend to prioritize intra‐team over inter‐team communications (Allen et al, 2014; Wang et al, 2015). This tendency to favour intra‐team communications is more likely to happen when under stress (Campbell et al, 2022) and when organizations lack a culture of information sharing (Bharosa et al, 2010; Kwon et al, 2011). Within emergency response contexts, it has been shown that processes for information sharing are not embedded; the Manchester Arena Inquiry (Saunders, 2022) noted there was a failure to identify who needed specific pieces of information, there were no clear radio channels to communicate information, and agencies failed to co‐locate at the scene limiting communications.…”
Section: Resultsmentioning
confidence: 99%
“…79 Overall, a failed MTS can be defined as an MTS whose performance, in the face of challenges, resulted in a failure to achieve targeted distal goals. 80 In their historiometric analysis of failed MTS performance, Campbell and colleagues 80 identified four major themes that were found across or seen as a contributing factor in known cases of MTS breakdown. Using the action subphases or team alignment behaviors (acting, monitoring, and recalibrating) at the within-and betweenteams levels from Torres et al 78 as the foundation for their evaluation, they noted that failing MTSs demonstrated an imbalance in withinteam alignment behaviors more often than and at the expense of between-team alignment behaviors.…”
Section: The Concept Is Especially Relevant For Understanding Teamwor...mentioning
confidence: 99%
“…Real‐world cases of failed MTSs can range from extreme, high‐stakes contexts such as the 2017 collision of three U.S. Navy vessels, resulting in the deaths of several Navy sailors and millions of dollars in damages, 78 to less extreme contexts such as the 2013 failed launch day for the Affordable Care Act website, which saw more than 250 000 users, of which only six were able to select a plan and submit an application 79 . Overall, a failed MTS can be defined as an MTS whose performance, in the face of challenges, resulted in a failure to achieve targeted distal goals 80 …”
Section: Opportunities For Learning Health Systemsmentioning
confidence: 99%
“…Multiteam systems operate in high-stakes and dynamic environments that require deep coordination of actions and responses, tracking and monitoring information, sharing and information exchange, and adapting actions as new information or exchanges occur both within and across teams [5,6]. This creates a situation with important consequences for suboptimal performance [6]. The demands of multiteam systems increase the challenges of creating cohesive, interdependently functioning and high-performing teams that enhance effectiveness for both members and patients.…”
mentioning
confidence: 99%
“…provide high-quality and safe patient care). Multiteam systems operate in high-stakes and dynamic environments that require deep coordination of actions and responses, tracking and monitoring information, sharing and information exchange, and adapting actions as new information or exchanges occur both within and across teams [5,6]. This creates a situation with important consequences for suboptimal performance [6].…”
mentioning
confidence: 99%